PENGARUH PEMAHAMAN DAN AKSES MEDIA INFORMASI TENTANG ZAKAT TERHADAP MINAT MUZAKKI MEMBAYAR ZAKAT - Fitri Fitri; Efni Anita; Nurlia Fusfita (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This research aims to describe and see the influence of understanding and access to information media about zakat on muzakki's interest in paying zakat in Jambi City. The method used in this research is quantitative descriptive with multiple linear regression analysis. The research samples were selected using purposive sampling technique, namely 96 samples. The research results show that the variables of understanding and access to information media have a significant effect, both partially and simultaneously. Partially, the understanding variable has a significance value of 0.000<0.05. Access to information media has a significance value of 0.000<0.05. Based on this research, researchers suggest that (1) the government and zakat management institutions utilize online media platforms to provide information about zakat, (2) the public to seek information and understand the importance of zakat, (3) researchers further examine the factors that influence interest in muzakki and pay other zakat.